2018
DOI: 10.1101/299073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous fluctuations of OCT4 and SOX2 bias pluripotent cell fate decisions

Abstract: SOX2 and OCT4 are pioneer transcription factors playing a key role in embryonic stem (ES) cell self-renewal and differentiation. However, how temporal fluctuations in their expression levels bias lineage commitment is unknown. Here we generated knock-in reporter fusion ES cell lines allowing to monitor endogenous SOX2 and OCT4 protein fluctuations in living cells and to determine their impact on mesendodermal and neuroectodermal commitment. We found that small differences in SOX2 and OCT4 levels impact cell fa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Additionally, the expression of the TFs-YPet can be turned on when desired, which is essential for many of the experiments described below. A previous work shows that the fluorescent TFs present similar genome-wide binding profiles to those obtained for the untagged TFs and that the expression of the fluorescently-tagged TFs rescues pluripotency of Oct4 or Sox2 knockout ES cells 26 .…”
Section: Generation Of Mouse Embryonic Stem Cell Lines With Doxycyclimentioning
confidence: 66%
“…Additionally, the expression of the TFs-YPet can be turned on when desired, which is essential for many of the experiments described below. A previous work shows that the fluorescent TFs present similar genome-wide binding profiles to those obtained for the untagged TFs and that the expression of the fluorescently-tagged TFs rescues pluripotency of Oct4 or Sox2 knockout ES cells 26 .…”
Section: Generation Of Mouse Embryonic Stem Cell Lines With Doxycyclimentioning
confidence: 66%
“…Single-cell half-lives were not correlated with the initial integrated SNAP fluorescence intensity (Figures S4B and S4C; Table S3), suggesting that the observed variability is not due to an overexpression artifact. In addition, we measured the half-life of endogenous SOX2 using a knockin cell line in which both SOX2 alleles are endogenously fused to a SNAP-tag (Strebinger et al, 2018) and found similar average SOX2 half-lives and variability as for the corresponding dox-inducible cell line ( Figure 4B). To further confirm that the observed cell-to-cell variability in half-lives is not merely due to uncertainty in single-cell measurements and/or exponential fittings, we generated three cell lines in which we expressed both a SNAP-tagged and a Halo-tagged (Los et al, 2008) fusion of the same protein, both under the control of a dox-inducible promoter ( Figure 4C).…”
Section: Protein Degradation Rates Vary Significantly Between Single mentioning
confidence: 84%
“…Importantly, the fluorescence decay in either channel was not affected by photobleaching ( Figure S4G). In addition, we also monitored the SNAP/Halo decay in a SOX2-SNAP/OCT4-Halo knockin cell line (Strebinger et al, 2018) and observed a high correlation of endogenous SOX2 and OCT4 protein halflives in individual cells ( Figure 5B; Table S3). Next, we measured single-cell protein half-lives in NIH 3T3 fibroblasts, and found similar ranges of intercellular variability in protein degradation rates, as well as similar coefficients of variations ( Figures 5C and S5A).…”
Section: Cell-to-cell Variability In Half-lives Is Caused By Heterogementioning
confidence: 99%
“…The popularity of the transcriptional bursting model is evident by the large number of papers that fit the entire RNA and protein distributions to the two‐state model without considering other sources of variability (Skupsky et al , ; Suter et al , ; Molina et al , ; Dey et al , ). In other cases, cell state was considered using dual reporters (Sigal et al , ; Strebinger et al , ), assuming timescale separation (Dar et al , ), or conditioning on forward scatter (Sherman et al , ). However, without multiplexed expression measurements it is difficult to determine whether conditioning on cell state was done to completion.…”
Section: Discussionmentioning
confidence: 99%